Initial experience using a novel algorithm to calculate omnipolar electrograms using a high-density grid-style catheter. (19th May 2022) - Kottmaier, M; Inaba, O; Phillips, K; Adsett, M; Hayes, J; Gkalapis, C; Lengauer, S; Clementy, N; Bailey, C; Kaneko, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: A novel mapping algorithm recently became available in Europe and select countries in the Asia Pacific region. EnSite Omnipolar Technology (OT) utilizes the Advisor HD Grid Mapping Catheter, Sensor Enabled (HD Grid) to calculate electrograms in 360 degrees from two bipolar and three unipolar electrograms acquired from a triangular set of three electrodes. This software also enables calculation of wavefront characteristics including maximum voltage, activation direction and wave speed. Procedural characteristics and clinical utilization of this novel software have not yet been reported. Purpose: To examine the clinical utility and procedural characteristics associated with the use of this novel mapping algorithm among participating centers. Methods: Acute procedural data were prospectively collected in 386 cases at 52 centers utilizing the newly approved mapping software in the initial phases of commercialization in Europe and the Asia Pacific region. Procedural characteristics recorded included indication for mapping/ablation, navigation mode, mapping reference, and maps and tools used to diagnose/locate ablation targets. Results: A total of 14 indications for mapping and ablation were represented including AF, atypical flutter, and VT (Table 1). VoXel (magnetic primary) navigation mode was used in most cases (n=325, 84%). The CS catheter was used as the map reference in 280 cases (73%). A variety of workflows were used with OT to diagnose and locate ablation targets including voltage maps (n=275, 71%), LAT maps (n=226, 59%), OT activation vectors (n=124, 32%), propagation maps (n=94, 24%), and sparkle maps (n=69, 18%); note: total exceeds 100%, multiple workflows per case observed. EnSite LiveView Dynamic Display (LiveView) was used in 129 cases (33%) to diagnose and locate ablation targets, including 28 (22%) where OT activation vectors were used with LiveView. Several benefits of OT were reported including rapid identification of ablation target(s) (n=133, 35%), higher point density (n=82, 21%), better signals (n=69, 18%), and improved procedure efficiency (n=48, 12%). Conclusion(s): Initial experience with this novel mapping software in Europe and the Asia-Pacific region illustrated utility in a variety of arrhythmias to diagnose and locate ablation targets. The use of OT provided several benefits including rapid identification of ablation targets and higher point density, however further examination of its impact on procedural efficiencies and acute outcomes is likely warranted.